2011
DOI: 10.1074/jbc.r111.233981
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Recombination of Herpes Simplex Virus DNA

Abstract: Replication of herpes simplex virus takes place in the cell nucleus and is carried out by a replisome composed of six viral proteins: the UL30-UL42 DNA polymerase, the UL5-UL8-UL52 helicase-primase, and the UL29 single-stranded DNA-binding protein ICP8. The replisome is loaded on origins of replication by the UL9 initiator origin-binding protein. Virus replication is intimately coupled to recombination and repair, often performed by cellular proteins. Here, we review new significant developments: the three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 83 publications
(71 reference statements)
1
39
0
Order By: Relevance
“…Results presented above and previously published observations demonstrate direct interactions between UL8 and UL5-UL52 as well as ICP8 (1,8). It has also been suggested that UL8 interacts directly with OBP and the UL30 catalytic subunit of DNA polymerase (11,12).…”
Section: Ul8/ul52 Interaction In the Herpesvirus Replisomesupporting
confidence: 68%
“…Results presented above and previously published observations demonstrate direct interactions between UL8 and UL5-UL52 as well as ICP8 (1,8). It has also been suggested that UL8 interacts directly with OBP and the UL30 catalytic subunit of DNA polymerase (11,12).…”
Section: Ul8/ul52 Interaction In the Herpesvirus Replisomesupporting
confidence: 68%
“…DNA viruses are the smallest self-replicating entities, and specific palindromic sequences are required for their replication. 7,8 In most cases, the main initiating protein is encoded by the viral genome itself. Its binding to the Ori is also actively involved in the regulation of viral transcription and chromosomal segregation.…”
Section: New Insights Into Replication Origin Characteristics In Metamentioning
confidence: 99%
“…We hypothesized that if herpesviral DNA replication is fully functional in the absence of PCNA, DNMT1 could not be recruited to the replication forks of the herpesviral DNA. As herpesviruses overreplicate, i.e., amplify their DNA several hundredfold during the lytic phase (37,43), methylation marks at cytosine residues would be lost on both newly synthesized DNA strands, removing this epigenetic modification from EBV's genomic DNA, which had been acquired during latency.…”
mentioning
confidence: 99%
“…Viral but not cellular factors mediate lytic herpesviral DNA replication (15,20,37). The function of PCNA in viral DNA replication is replaced by a structural homologue encoded by all herpesviruses, termed UL42 and BMRF1, in herpes simplex 1 and Epstein-Barr virus, respectively.…”
mentioning
confidence: 99%